"Dangerous liaisons: NAFLD and liver fibrosis increase cardiovascular risk in HIV". Issue 8 (24th February 2022) - Cervo, Adriana; Sebastiani, Giada; Milic, Jovana; Krahn, Thomas; Mazzola, Sergio; Petta, Salvatore; Cascio, Antonio; Guaraldi, Giovanni; Mazzola, Giovanni
Abstract: Objectives: Non‐alcoholic fatty liver disease (NAFLD) is strongly associated with cardiovascular disease in the general population. We aimed to assess the impact of NAFLD and liver fibrosis on intermediate‐high cardiovascular risk in people living with HIV. Methods: We included people living with HIV from three cohorts. NAFLD and significant liver fibrosis were defined using transient elastography: controlled attenuation parameter ≥288 dB/m and liver stiffness measurement ≥7.1 kPa, respectively. Cardiovascular risk was assessed with the atherosclerotic cardiovascular disease (ASCVD) risk estimator in patients aged between 40 and 75 years and categorised as low if <5%, borderline if 5%–7.4%, intermediate if 7.5%–19.9% and high if ≥20% or with the presence of a previous cardiovascular event. Patients with hepatitis B and/or hepatitis C virus co‐infection, alcohol abuse and unreliable transient elastography measurements were excluded. Predictors of intermediate‐high cardiovascular risk were investigated in multivariable analysis by logistic regression and also by stratifying according to body mass index (BMI; cut‐offs of 25 and 30 kg/m 2 ) and age (cut‐off of 60 years). Results: Of 941 patients with HIV alone included, 423 (45%), 128 (13.6%), 260 (27.6%) and 130 (13.8%) were categorised as at low, borderline, intermediate and high ASCVD risk, respectively. Predictors of intermediate‐high ASCVD risk were NAFLD (adjusted odds ratio [aOR] 2.11; 95% confidence interval [CI] 1.40–3.18; p  < 0.001), liver fibrosis (aOR 1.64; 95% CI 1.03–2.59; p  = 0.034), duration of HIV (aOR 1.04; 95% CI 1.02–1.06; p  < 0.001), and previous exposure to thymidine analogues and/or didanosine (aOR 1.54; 95% CI 1.09–2.18; p  = 0.014). NAFLD was also associated with higher cardiovascular risk in normoweight patients (aOR 2.97; 95% CI 1.43–6.16; p  = 0.003), in those with BMI <30 kg/m 2 (aOR 2.30; 95% CI 1.46–3.61; p  < 0.001) and in those aged <60 years (aOR 2.19; 95% CI 1.36–3.54; p  = 0.001). Conclusion: Assessment of cardiovascular disease should be targeted in people living with HIV with NAFLD and/or significant liver fibrosis, even if they are normoweight and young.